Safety and tolerability of intravitreal cetuximab in young and adult rabbits - Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Panda-Jonas, Songhomitra; Khakimov, Dinar A.; Gilemzianova, Leisan I.; Miniazeva, Liana A.; Tuliakova, Azaliia M.; Fakhretdinova, Albina A.; Kazakbaev, Renat A.; Nuriev, Ildar F.; Jonas, Jost B. (Scientific reports, 2022)
To assess safety and tolerability of intraocularly applied cetuximab as epidermal growth factor receptor antibody, we conducted the experimental study which consisted of groups of adult rabbits (body weight: 2.4 kg) and young rabbits (body weight: 1.6 kg). All animals received three intravitreal injections of 0.5 mg cetuximab (Erbitux) (0.10 mL; 5 mg cetuximab/mL) into their right eyes in 4-week intervals, while the contralateral eyes received intravitreal injections of Ringer's solution. All animals underwent regular ophthalmological examinations at baseline and two-week intervals. Four weeks after the last injection, the animals were sacrificed, and the eyes were enucleated, fixed and examined by light microscopy. The study included 10 adult rabbits (age: 18 weeks; range: 17–19 weeks) and 8 young rabbits (age: 8 weeks; range: 7–10 weeks). Biometric measurements of axial length, anterior chamber depth and lens thickness and intraocular pressure readings did not differ significantly (all P > 0.05, Bonferroni corrected) between the right (study) eyes and the left (control) eyes, neither in the young nor in the adult rabbit group. Signs of intraocular inflammation or fundus peculiarities were not detected. Thickness of the outer nuclear layer, inner nuclear layer, combined outer and inner nuclear layer and outer plexiform layer, and total retina, measured at the posterior pole, posterior pole/equator midpoint, equator, and ora serrata region, did not vary significantly between study eyes and control eyes (all P > 0.05, Bonferroni corrected). The results suggest that repeated intravitreal application of cetuximab did not result in any detected intraocular toxic or destructive effect in young and adult rabbits, concurring with the notion of an intraocular tolerability of cetuximab.